CIP's sweet potato genebank develops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Since 1985 CIP (The International Potato Center) has assembled one of the largest existing collections of Ipomoea batatas (sweet potato) and the wild species related to this crop. Numerous sites have been found where large populations of wild...